MEETING AMONG SCREENS: ONLINE GROUP INTERVIEW AS A RESEARCH DATA PRODUCTION DEVICE - Silva de Moura, Aline (2024)
The online group interview is the subject of this study, emerging from a doctoral process developed during the COVID-19 pandemic. It's an account of experimenting with virtual group interviews as a data production tool for a qualitative health research that used cartography as a reference. We will address the management, boundaries, and challenges of an online group interview conducted in August 2021, involving seven participants. The strategy enabled bringing together participants from diverse geographical backgrounds and fields of study, while also serving as a tool for facilitating encounters and reflective practice.